Minimising the Risk: Teen Perspectives on Sexual Choking in Pornography - Woodley, Giselle; Jaunzems, Kelly (M/C - Media and Culture, 2024)
Sexual choking / strangulation encompasses a range of practices where pressure is applied to the neck to restrict air or blood flow during a sexual encounter. While choking is most commonly associated with the application of hands around a person’s neck, other limbs or ligatures, such as the forearm or rope, may also be used (Herbenick et al., Frequency 3122; Herbenick et al., Prevalence 1059). This article will predominantly use the term “choking” or “sexual choking” to match teen vernacular and public discourse. These terms, however, may be used interchangeably with other more context-specific terms used in the literature such as “breath play”, “strangulation”, “erotic asphyxiation”, and “sexual asphyxia” (Cardoso 1070; Vilhjálmsdóttir and Forberg 4).